Quantifying the power and consequences of social media protest. (March 2018) - Freelon, Deen; McIlwain, Charlton; Clark, Meredith
The exercise of power has been an implicit theme in research on the use of social media for political protest, but few studies have attempted to measure social media power and its consequences directly. This study develops and measures three theoretically grounded metrics of social media power—unity, numbers, and commitment—as wielded on Twitter by a social movement (Black Lives Matter [BLM]), a counter-movement (political conservatives), and an unaligned party (mainstream news outlets) over nearly 10 months. We find evidence of a model of social media efficacy in which BLM predicts mainstream news coverage of police brutality, which in turn is the strongest driver of attention to the issue from political elites. Critically, the metric that best predicts elite response across all parties is commitment.